Propuesta de un plan de implementación de un sistema de gestión de calidad basado en los requisitos de la norma ISO 9001:2015 para la empresa SSH S.A (2021)
The following work presents a proposal for an implementation plan of a Quality Management System (QMS), according to the ISO 9001: 2015 standard for the company SSH S.A. (Software, Servicios y Hardware S.A.), an SME in the information and communication technology sector. The work was carried out in four stages, in the first one the analysis of the organizational context was carried out through the use of the matrices of evaluation of internal factors (EFI) and external (EFE), the matrix of analysis of political, economic factors, social, technological, ecological and legal (PESTEL), a checklist of needs and expectations of interested parties and a review of the mission, vision and values of the company. In the second stage, the identification and characterization of the processes was carried out using a characterization matrix, later a process map was established to define the interactions between them. As a third stage, a diagnosis of the company was carried out against the requirements of the ISO 9001: 2015 standard using a checklist to determine its compliance status. Finally, as the last stage, an action plan was created which includes the activities to be carried out in order to achieve the implementation of the QMS.